Analysis of ethics dumping and proposed solutions in the field of biomedical research in China - Liao, Bohua; Ma, Yonghui; Lei, Ruipeng (Frontiers in Pharmacology, 2023)
As international academic exchanges and cooperation deepen, China has actively engaged in international biomedical research collaboration and achieved significant success. However, these accomplishments have been accompanied by ethical controversies and issues, with ethics dumping being a recurrently discussed focus among scholars. This paper reviews ethics dumping incidents in China’s biomedical research field and analyzes the underlying causes to answer why China is often susceptible to ethics dumping. We argue that the primary reasons include weak ethical awareness among some researchers, an oversimplified research evaluation system, gaps in relevant ethics governance and oversight mechanisms, and limited capabilities of certain ethics committees. To address these issues, we propose five ethics governance recommendations: establishing refined ethics committees at various levels and types; advancing theoretical and practical research on science and technology ethics governance; strengthening legislation and regulation related to emerging science and technology; emphasizing self-regulation and capacity building of research institutions; and providing special protection and healthcare for victims of ethics dumping. The aim is to enhance China’s research supervision system and prevent similar ethics dumping incidents from recurring.